Outcomes of a co-located approach for metabolic health care for people with schizophrenia. (August 2022) - Siskind, Dan; Yen, Wesley; Thuzar, Moe; Russell, Anthony; Warren, Nicola; Kisely, Steve; Kar Ray, Manaan; Motamarri, Balaji
Objective: Metabolic syndrome is highly prevalent among people with schizophrenia. This study aims to assess the impact on metabolic and attendance outcomes of a co-located, dedicated, endocrinologist-led metabolic clinic in a stand-alone public community mental health service. Methods: Demographic and metabolic data on the first 48 consecutive referrals over a 12-month period were retrospectively collected and analysed. Attendance rates at the co-located clinic were compared to the general hospital obesity and diabetes clinics. Results: Clinic attendees had significant reductions in triglycerides and total cholesterol, but not mean weight, BMI, waist circumference, blood pressure or HbA1c. Attendance rates were significantly higher in the co-located clinic compared to the general hospital obesity and diabetes clinics for both initial consult (80.0% vs 51.2%, p < 0.001) and review appointment (64.3% vs 47.6%, p < 0.001). Conclusion: The co-location of a specialist metabolic clinic within a mental health service resulted in enhanced engagement and improvement of metabolic health in people with schizophrenia.